An Ecological Call to Arms: The Air of Death and the Origins of Environmental Activism in Ontario - O’Connor, Ryan (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
This article argues that the 22 October 1967 broadcast of The Air of Death was a central event in the emergence of environmental activism in Ontario. A production of the Canadian Broadcasting Corporation, The Air of Death examined air pollution’s adverse impact upon the environment. This documentary drew the ire of industrial interests as a result of its allegations of human fluorosis poisoning in Dunnville, Ontario. Subsequently, the film and the team behind it were subjected to two high-profile investigations, an Ontario ordered Royal Commission and a Canadian Radio-Television Commission hearing. This controversy resulted in the creation Ontario’s first two environmental activist organizations, most notably the highly influential Pollution Probe at the University of Toronto, which would play a key role in shaping the province’s nascent environmental community.